Adaptability and stability of early sugarcane genotypes in Rio Grande do Sul, Brazil - Verissimo, Mario Alvaro Aloisio; Silva, Sérgio Delmar dos Anjos e; Aires, Rogério Ferreira; Daros, Edelclaiton; Panziera, Wildon (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the adaptability and stability of early maturation sugarcane genotypes, as to yield of stalk and Brix, in Rio Grande do Sul state, Brazil. Fifteen early‑maturing genotypes were evaluated in the 2009/2010 and 2010/2011 seasons, through the additive main effects and multiplicative interaction (AMMI) analysis. Genotype x environment interactions were highly significant and evidenced changes in the genotype ranking according to the environment. New genotypes exceeded the standard early genotype RB855156 for productivity and stability, although it still stands out for its high productivity, moderate stability and wide adaptability. Genotype RB966928 stood out for its richness and yield of Brix, moderate stability and wide adaptability. Salto do Jacuí, RS, Brazil, is the most suitable site for preliminary tests of genotype selection.